Legalitas Akad Hybrid dalam Fintech Syariah: Studi Kasus Pembiayaan Murabahah-Ijarah dan Tantangan Hukum dalam Penyelesaiannya - Nafoura Maharani Arl; Baidhowi Baidhowi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the legality of hybrid contracts in Islamic fintech with a focus on the combination of murabahah and ijarah contracts in the financing scheme. Hybrid contracts are an innovative solution in the Islamic financial system, but still face legal challenges, especially in legal certainty, consumer protection, and dispute resolution. This study uses the normative juridical method with a statutory approach and analysis of default cases on one of the Islamic fintech platforms in Indonesia. The results of the study show that existing regulations, such as the DSN-MUI fatwa and POJK related to Islamic fintech, have not fully provided clarity regarding the hybrid scheme, especially in terms of risk mitigation and dispute resolution mechanisms. In addition, there are still differences in interpretation in the application of hybrid contracts that can potentially cause legal uncertainty for business actors and customers. The conclusion of this study emphasizes the need for regulatory harmonization and improvement of supervisory and dispute resolution mechanisms in Islamic fintech in order to ensure the sustainability and legal certainty in the implementation of hybrid contracts.